Gutta-percha points surface alterations after sodium hypochlorite disinfection - Brito, Selma Maria Santos Moura; Vasconcelos, Rafaela Andrade de; Oliveira, Simone Helena Gonçalves de (Brazilian Dental Science, 2013)
The gutta-percha should be disinfected before the shutter from being a vehicle for microorganisms to periapical tissues. Whereas cones may remain for longer than necessary for the disinfection immersed in disinfectant solutions, evaluated the effect of 1% and 2,5% NaOCl, on the surface morphology of gutta-percha as a function of immersion time. Analyzed by SEM (scanning electron microscope) the surface morphology of 110 gutta-percha main divided into three groups: G1 (control): no disinfection, disinfection in 1% NaOCl for 20 min, 2,5% NaOCl for 10 min; G2 disinfection in 1% NaOCl for 30 min, 6h,12h and 24 h; G3 disinfection in 2,5%NaOCl for 30 min, 6h,12h and 24h. The images were obtained by SEM, the apex of the cones were photographed at 500x and 5000x increased and qualitatively analyzed for the presence of surface changes. The results showed a gradual change in surface morphology of the growing cones with increasing concentration of NaOCl and immersion time. The controls group (G1) showed minimal change in surface cones. It is conclude that by increasing the concentration of NaOCl solution and immersion time of gutta-percha increasing changes occur on the outer surface of the cone.Keywords: Disinfection, Endodontics, Gutta-percha, Sodium hypochlorite